Scaling up of HIV treatment for men who have sex with men in Bangkok: a modelling and costing study. Issue 5 (May 2015) - Zhang, Lei; Phanuphak, Nittaya; Henderson, Klara; Nonenoy, Siriporn; Srikaew, Sasiwan; Shattock, Andrew J; Kerr, Cliff C; Omune, Brenda; van Griensven, Frits; Osornprasop, Sutayut; Oelrichs, Robert; Ananworanich, Jintanat; et al.
Summary: Background: Despite the high prevalence of HIV in men who have sex with men (MSM) in Bangkok, little investment in HIV prevention for MSM has been made. HIV testing and treatment coverage remains low. Through a pragmatic programme-planning approach, we assess possible service linkage and provision of HIV testing and antiretroviral treatment (ART) to MSM in Bangkok, and the most cost-effective scale-up strategy. Methods: We obtained epidemiological and service capacity data from the Thai National Health Security Office database for 2011. We surveyed 13 representative medical facilities for detailed operational costs of HIV-related services for sexually active MSM (defined as having sex with men in the past 12 months) in metropolitan Bangkok. We estimated the costs of various ART scale-up scenarios, accounting for geographical accessibility across Bangkok. We used an HIV transmission population-based model to assess the cost-effectiveness of the scenarios. Findings: For present HIV testing (23% [95% CI 17–36] of MSM at high risk in 2011) and ART provision (20% of treatment-eligible MSM at high risk on ART in 2011) to be sustained, a US73·8 million (51·0 million to 97·0 million) investment during the next decade would be needed, which would link an extra 43 000 (27 900–58 000) MSM at high risk to HIV testing and 5100 (3500–6700) to ART, achieving an ART coverage of 44% for MSM at high risk in 2022. An additional 55·3 million investment would link an extra 46 700 (30 300–63 200) MSM to HIV testing and 12 600 (8800–16 600) to ART, achieving universal ART coverage of this population by 2022. This increased investment is achievable within present infrastructure capacity. Consequently, an estimated 5100 (3600–6700) HIV-related deaths and 3700 (2600–4900) new infections could be averted in MSM by 2022, corresponding to a 53% reduction in deaths and a 35% reduction in infections from 2012 levels. The expansion would cost an estimated 10 809 (9071–13 274) for each HIV-related death, 14 783 (12 389–17 960) per new infection averted, and 351 (290–424) per disability-adjusted life-year averted. Interpretation: Spare capacity in Bangkok's medical facilities can be used to expand ART access for MSM with large epidemiological benefits. The expansion needs increased funding directed to MSM services, but given the epidemiological trends, is probably cost effective. Our modelling approach and outcomes are likely to be applicable to other settings. Funding: World Bank Group and Australian National Health and Medical Research Council.